Pelvic sepsis following laparoscopic appendicectomy versus open appendicectomy: a retrospective study of 648 cases - Adams, Hannah L.; Jaunoo, Sheik S. (International Surgery Journal, 2016)
Background:The purpose of this retrospective study was to evaluate the development of postoperative pelvic collections following Laparoscopic Appendicectomy (LA) and Open Appendicectomy (OA). Methods:A retrospective analysis of all patients undergoing emergency appendicectomy between February 2010 and January 2012 at a single UK tertiary care referral centre were considered for inclusion in this study. Data collection was undertaken and analysed using descriptive statistics. Results:Of the 648 appendicectomies (361 male, 287 female), 177 were performed laparoscopically. Histology confirmed appendicitis in 484 patients. There were 19 cases of pelvic sepsis (LA n=2, OA n=17), not statistically significant (p=0.1184). Conclusions:Laparoscopic appendicectomy is a safe operative procedure and is not associated with an increased risk of pelvic sepsis.